Penguatan Perlindungan Nelayan dalam Blue Economy: Analisis Kerangka Hukum dan Pendanaan di Kabupaten Indramayu - Syahuri, Taufiqurrohman; Kaharuddin, Kaharuddin; Sadiawati, Diani; Dirkareshza, Rianda; Fauzan, Muhammad (Morality: Jurnal Ilmu Hukum, 2024)
The entire world agrees that in supporting sustainable development, it must comply with the 17 points of sustainable development goals, one of which is point 14 which believes in sustainability in the marine ecosystem. Fishermen are one of the things that support the blue economy. However, in terms of protection, it is inadequate in the absence of protection arrangements at the regional level through Regional Regulations as mandated by Law No. 7 of 2016 concerning Protection and Empowerment of Fishermen, Fish Cultivators, and Salt Farmers, especially in the Majakarta area, Indramayu Regency, West Java. This research aims to find out how the ideal regulation regarding the protection and funding of fishermen in Indramayu Regency because there is no regulation at the local regulation level in terms of protection. The method used in this research is empirical juridical with legislative approach, comparative approach, and conceptual approach. In determining the concept of protection and funding in technical local regulations, it has not been regulated in a regional context. Moreover, the level of regional regulations in Indramayu Regency has not accommodated the protection of fishermen comprehensively. Thus, further regulation is needed at the regional regulation level by prioritizing the active role of fishermen in accessing funding at the district government in order to obtain legal protection.